2005
DOI: 10.1158/1055-9965.144.14.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Single Nucleotide Polymorphism in the Insulin-Like Growth Factor I Regulatory Region Associates with Colorectal Cancer Risk in Singapore Chinese

Abstract: Elevated levels of plasma insulin-like growth factor I (IGF-I) are a potential risk factor for several cancers, including colorectal cancer. Physiologic levels of plasma IGF-I vary greatly; this variation may be in part genetically determined. We identified two single nucleotide polymorphisms (SNP) in perfect linkage disequilibrium with each other and in partial linkage disequilibrium with a previously studied cytosine-adenine microsatellite [-969(CA)n]. We investigated one of the SNPs, -533T/C,and the 969(CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…found no association between risks of CRC and IGF1 genotypes [-969(CA)19, -969(CA)18] in the 290 case and 873 control from Chinese population. However, they found that CA(21) was associated with CRC risk (P=0.02) ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…found no association between risks of CRC and IGF1 genotypes [-969(CA)19, -969(CA)18] in the 290 case and 873 control from Chinese population. However, they found that CA(21) was associated with CRC risk (P=0.02) ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for other polymorphisms located in the promoter region of IGF1, some studies have investigated the role of rs5742612T>C and rs12579108C>A. In 290 Chines patients, CC and CT genotypes of rs5742612T>C were associated with a decreased risk of CRC (Pvalue not reported), and a protective effect of the C allele was observed among participants younger than 60 years (30). However, Mahmoudi et al found no association of rs5742612T>C with risk of CRC in 261 Iranian patients (41).…”
Section: Figurementioning
confidence: 99%
“…The IGFBP3 promoter region A-202C polymorphism (rs1805086) can influence circulating IGFBP3 levels with the C allele expressing significantly lower activity compared with the A allele, resulting in lower circulating IGFBP3 levels (29,36). IGFBP3 levels are regulated by GH and serve as a reservoir of IGF1, and therefore, IGFBP3 low levels may reflect lower IGF1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, associations of these candidate variants with CRC susceptibility were found in a relatively small number of studies and were rarely replicated. Reports include both potentially functional and tagging variants within IGF-I (rs12423791, rs1019731, rs5742632, rs5742678, rs5742694, rs2033178, rs2373722, rs1520220, rs10735380, rs6220, rs6214, rs35767, 19-CA repeat polymorphism), IR (rs10426094, rs1052371), IGFBP-3 (rs2854744, rs2854746, rs3110697, rs2132572, rs35440925), IGF1R (rs2229765, rs7166348), IRS-1 (rs1801278) and IRS-2 (rs1805097, rs2289046, rs754204, rs4773082) [ 68 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ].…”
Section: Insulin-like Growth Factors and Colorectal Cancermentioning
confidence: 99%